EKSTRAKSI ZAT WARNA ALAMI BUNGA TELANG DENGAN METODE EKSTRAKSI SOKLETASI - Sofiah (KINETIKA, 2022)
The Butterfly Pea (Clitoria ternatea) is one of the plants whose all parts have functional benefits for the human body. Theflower petals are reported to be useful as antioxidants, antidiabetic, antiobesity, anticancer, anti- inflammatory, antibiotic andprotect liver issue. One of the natural pigments that may be used as natural dyes is anthocyanin. Butterfly Pea (Clitoriaternatea) is a source of blue pigment or anthocyanin. One of the ways so thatthe butterfly pea can be consumed by the public isby utilizing the potential of natural pigments from the extract ofthe telang flower and some of the content in it can be done byapplying it as a natural food coloring. This is one of the efforts that can be done to prevent the increasing use of unsafesynthetic dyes by replacing them with the manufacture of natural dyes. Anthocyanin is a natural pigment that gives blue colorto the butterfly pea (Clitoria ternatea). Anthocyanin extraction using soxhletation method with aquadest solvent and extractiontime (90, 120 and 150 minutes). This study aims to determine the best extraction time for the extraction of anthocyanins frombutterfly pea. The research parameters included qualitative and quantitative analysis of anthocyanins (extract yield, totalanthocyanin concentration, and antioxidant activity) of butterfly pea extract. From the results of the study, it was found thatthe best condition is extract with time variation 90 minutes and 10 times circulation using aquades as a solvent with extract ofyield 2.36%, total of anthocyanin concentration 80.105 mg/L, and antioxidant with IC50 35.91.